Retrospective study of 32 encephalic tumors diagnosed by advanced - image magnetic resonance imaging and computed tomography - Benavides, Henry (2011)
The incidence of encephalic tumors in dogs and cats has increased in recent years due to the constant advancement of methods of specialist Diagnostic Imaging: Magnetic Resonance Imaging (MRI) and Computed Tomography (CT), used in small animals. These tools, which were distant in the past, are now becoming increasingly important as an additional aid to the identification of tumor processes in the Central Nervous System. The objective, of the present study, was describe imaging findings obtained in 32 cases of encephalic tumors, through techniques of CT and MR imaging procedures during the years 2004 to 2011. Were diagnosed 19/32 by MRI and 13/32 by CT, being the most affected breed Boxer (9/32), the mean age was 10 years.